The Effects of Online Learning Management Towards English Grammar Achievement of Business English Students - Kunlasuth, Kanokwan; Jatepanjapak, Sudarat; Chaovanapricha, Khacheenuj; Chirasawadi, Sarapol; Ploylearmsaeng, Wilasinee; Poolsub, Lalita; Panasri, Chulaluk (Suan Dusit Graduate School Academic Journal, 2021)
This research study aimed to compare Business English students' achievement in English grammar before and after obtaining online learning management, and to explore their perceptions towards the development of English grammar knowledge. Quantitative and qualitative research were used. The subjects were 43 Business English senior students in Academic Year 2017 who did the tests and responded to the questionnaires and 5 students were purposively selected to have a group interview. Research instruments were the pretest-posttest, questionnaire and interview schedule. The content validity index of every question in the questionnaire was 1.00. Quantitative data were analyzed by frequency distribution, percentage, mean, standard deviation and dependent sample t-test. Major findings revealed that Business English students' achievement in English grammar improved after online self-study at the statistical significance level of .05. The students showed an agreement with the development of English grammar knowledge through online self-study. The first aspect showing a strong agreement indicated that students learned the content from online grammar exercises as much as they could. Findings from the interview revealed three aspects: being convenient for online self-study through Application, development of grammatical competence and an ability to apply their knowledge to take the TOEIC test.